Neural regulation of fear based on olfactory, visual and auditory sensory systems - Zhu Yimo (BIO Web of Conferences)
Fear is a ubiquitous emotion that is crucial to the survival and development of humans and animals. Mammals perceive potential dangers through various sensory systems, thereby defending against or avoiding dangers. With the development of biomedical technology, great progress has been made in the neural regulation mechanism of fear. The olfactory, visual and auditory systems play important roles in the regulation of innate fear and conditioned fear response. Among them, the olfactory system triggers fear response by detecting odor information through the main olfactory system and the accessory olfactory system. The visual system regulates fear response by transmitting visual information through subcortical pathways and sensory cortical pathways. The auditory system processes fear-related sound stimuli by transmitting sound information through structures such as the cochlear nucleus and thalamus. This article reviews previous studies and discusses the roles of three different sensory systems, namely vision, hearing and smell, in fear, which will help to gain a deeper understanding of the brain’s mechanism for processing fear and the role of different sensory systems in fear emotions.